MODEL PROSES DAN TAHAPAN SISTEMATIS DALAM INTERVENSI SOSIAL: PENDEKATAN TEORI DAN PRAKTIK - Adinda Putri Dewi; Adelia Citra Erlansyah, Salsabila Citra Dwi, Wanda Fitri Berliana, Zahwa Kania Putri, Tugimin Supriy (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Social intervention is an important strategy in addressing various social problems faced by individuals, groups, and communities, such as social inequality, addiction, and mental disorders. Although it has been widely implemented, many intervention programs fail to achieve optimal results due to a lack of in- depth understanding of the stages and roles of change agents in social interventions. This study aims to identify the main stages in the social intervention process model, as well as to understand the role of change agents in achieving positive social change. The method used in this study is a literature study with a thematic analysis approach, which examines various theories and practices of social intervention based on relevant academic sources. The results of the study indicate that the social intervention process model consists of stages such as problem identification, data collection, planning, implementation, monitoring, evaluation, and termination. Change agents play an important role in each stage, with the function of being a catalyst, solution provider, and resource connector. The conclusion of this study confirms that structured and data-based social interventions are very effective in achieving sustainable positive change in society. This study also proposes the need for further development through field research to obtain more in-depth primary data